Pelayanan Administrasi dan Umum di Kelurahan Plamongansari Kota Semarang Birokrasi, Mekanisme, Kinerja, dan Pemanfaatan Teknologi - Aditya Joshua K.; Khalimatus Sa'diyah; Maya Putri Amalia; Nofi Puji Lestari; Hesti Ristanto (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity was conducted at Plamongansari Urban Village, Semarang City, focusing on administrative and general public services. The identified issues included administrative service mechanisms, employee performance, utilization of service technology, and bureaucratic mechanisms in public administration. The objective of this community service was to describe and analyze the administrative and general service processes through direct assistance activities carried out by students. The method used was a participatory approach involving observation, direct assistance, and active involvement in administrative services at the urban village office. The results showed that administrative service mechanisms were implemented with clear procedures, the performance of public service personnel was relatively good, the utilization of service technology supported administrative efficiency, and bureaucratic mechanisms contributed to service orderliness. This community service activity also enhanced the awareness of public service personnel regarding professionalism, discipline, and community-oriented services. Therefore, this community service contributes to improving the quality of public services at Plamongansari Urban Village.